The Effect of Green Investment, Corporate Social Responsibility, and Good Corporate Governance on Green Company Value Mediated by Return on Investment - Gunawan, Salsabila Nadhifa; Sembiring, Ferikawita; Paramita, Santi (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2024)
Increasing company value indicates an increase in the company's share price on the stock exchange, which reflects the welfare of investors as company owners and capital owners. This research aims to analyze the influence of green investment, corporate social responsibility and good corporate governance on the green environment. company value with return on investment as a mediating variable (intervention). The research method used is a quantitative method. Data analysis used the path analysis method with E-VIEWS 12 data processing software. The sampling technique used the purposive sampling method. The number (size) of the sample consists of 16 companies (cross-section data) for 4 years (time series data), quarterly from 2020 to 2023. The combination of cross-section and time series data is a type of panel data which produces 192 data.The results of the research show that corporate social responsibility and good corporate governance as measured by independent commissioners, managerial ownership and institutional ownership can have a positive influence on the value of green companies which is mediated by return on investment as an intervening variable, but green investment does not can have a positive influence. The effect on green company value is mediated by return on investment as an intervening variable.